Hypercementosis: a challenge for endodontic therapy - Fernanda Geraldes Pappen; Cecilia Definski Fagonde2; Josué Martos; Luiz Fernando Machado Silveira (Revista Sul-Brasileira de Odontologia, 2012)
Introduction and objective: The purpose of this study was to describe through literature review, the morphological characteristics of teeth with hypercementosis that are relevant to endodontic practice. Literature review: The pathologic deposition of cement increases proportionally as the patient’s age increases. Genetic factors seem to be related to hypercementosis occurrence in young patients. Based on literature, it is possible to notice a lack of scientific studies which guide the endodontist for treating teeth with hypercementosis, since the cement deposition lead to the length increase of the cementum canal, and consequently, to the increase of the distance from CDC junction to apical root end. Conclusion: Thus, it is clinically relevant to correlate the morphology of teeth with hypercementosis with the specific aspects of endodontic therapy, aiming to establish the limits of root canal treatment in cases of hypercementosis.